Evaluation of cytotoxicity, antimicrobial activity and physicochemical properties of a calcium aluminate-based endodontic material - Emmanuel Joao Nogueira Leal SILVA; Daniel Rodrigo HERRERA; Tiago Pereira ROSA; Thais Mageste DUQUE; Rogerio Castilho JACINTO; Brenda Paula Figueiredo de Almeida GOMES; Alexandre Augusto ZAIA (University of São Paulo, 2014)
A calcium aluminate-based endodontic material, EndoBinder, has been developed in order to reduce MTA negative characteristics, preserving its biological properties and clinical applications. Objectives: The aim of this study was to evaluate the cytotoxicity, antimicrobial activity, pH, solubility and water sorption of EndoBinder and to compare them with those of white MTA (WMTA). Material and Methods: Cytotoxicity was assessed through a multiparametric analysis employing 3T3 cells. Antimicrobial activity against Enterococcus faecalis (ATCC 29212), Staphylococcus aureus. (ATCC 25923) and Candida albicans (ATCC 10556) was determined by the agar diffusion method. pH was measured at periods of 3, 24, 72 and 168 hours. Solubility and water sorption evaluation were performed following ISO requirements. Data were statistically analyzed by ANOVA and Tukey`s test with a significance level of 5%. Results: EndoBinder and WMTA were non-cytotoxic in all tested periods and with the different cell viability parameters. There was no statistical differences between both materials (P>.05). All tested materials were inhibitory by direct contact against all microbial strains tested. EndoBinder and WMTA presented alkaline pH in all tested times with higher values of pH for WMTA (P<.05). Both materials showed values complying with the solubility minimum requirements. However, EndoBinder showed lower solubility than WMTA (P<.05). No statistical differences were observed regarding water sorption (P>.05). Conclusion: Under these experimental conditions, we concluded that the calcium aluminate-based endodontic material EndoBinder demonstrated suitable biological and physicochemical properties, so it can be suggested as a material of choice in root resorption, perforations and root-end filling.